2017
DOI: 10.1017/s0022215117001384
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of injection laryngoplasty performed under local anaesthesia versus general anaesthesia: an Australian perspective

Abstract: Procedures performed under local anaesthesia in the operating theatre are associated with shorter operating theatre time and length of stay in the hospital, and provide significant cost savings. Further savings could be achieved if local anaesthesia procedures were performed in the office setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Though hospitalization was shorter in the conscious sedation group, the total costs were not significantly different. Further, studies describing the costs of different surgical interventions under local versus general anaesthesia found a significant reduction in cost when performing the intervention under local anaesthesia [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though hospitalization was shorter in the conscious sedation group, the total costs were not significantly different. Further, studies describing the costs of different surgical interventions under local versus general anaesthesia found a significant reduction in cost when performing the intervention under local anaesthesia [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…All articles used financial data based on actual cases, except for the studies of Castillo Farías et al [25] and Schutte et al [21], who estimated costs based on costs of materials, facilities and personnel required to perform these procedures in general. Hospital costs were discussed in seven studies [9, 10, 21, 22, 25-27]; hospital charges in eight studies [9, 11, 20, 23, 24, 27-29]. All included studies reported on costs from a hospital’s perspective.…”
Section: Resultsmentioning
confidence: 99%
“…The time frame in which financial data were collected ranged from 1995 to 2018. In the studies of Hillel et al [27] and Chandran et al [26], the analyzed costs were about awake surgery performed in the (in-hospital) endoscopy suite or instead of the office. The included parameters for costs or charges differed among studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations